A longitudinal investigation of parenting stress in caregivers of children with retinoblastoma. Issue 4 (3rd November 2016) - Willard, Victoria W.; Qaddoumi, Ibrahim; Zhang, Hui; Huang, Lu; Russell, Kathryn M.; Brennan, Rachel; Wilson, Matthew W.; Rodriguez‐Galindo, Carlos; Phipps, Sean
Abstract: Background: Retinoblastoma is typically diagnosed in young children and may present unique parenting challenges. Qualitative research suggests that parents experience distress related to the initial diagnosis and treatment that subsequently resolves. The objectives were to systematically assess parenting stress over time in parents of young children with retinoblastoma and to examine associations between parenting stress and child outcomes. Procedures: Parents of children with retinoblastoma completed the Parenting Stress Index (PSI) during serial psychological assessments scheduled based on the child's age (6 months to 5 years). Caregivers of 92 patients (85.9% mothers) completed the assessments. Child outcomes included developmental functioning and parent‐reported adaptive functioning. Results: At baseline and age 5, all subscales on the PSI were within normal limits, and most were significantly below normative means (i.e., demonstrating low levels of stress). All domains remained relatively stable over time. Associations between parenting stress and child outcomes were much stronger at age 5 than at baseline. Child‐directed parenting stress was a small but significant contributor to declines in child functioning over time. Conclusions: Parents of children with retinoblastoma report normal levels of parenting stress while their children are young. However, baseline parenting stress appears to contribute to changes in child functioning over time. Future studies should assess illness‐related aspects of adjustment to further understand the parenting experience of young children with cancer and/or having a visually impaired child.